(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2026)
The study aimed to determine how irrigation water from different sources affected the quality of three leafy vegetables in the Offinso Municipality of Ghana. For the study, a 5x3 factorial Completely Randomised Design (CRD) with three replications was used. Two factors were considered: irrigation water sources at five levels (wastewater, groundwater, tap water, well water, and rainwater), and leafy vegetables at three levels (cabbage, lettuce, and amaranthus). The proximate and mineral nutritional compositions of three leafy plants were analyzed. This study assessed the impact of various irrigation water sources on the nutritional quality of three leafy vegetables commonly cultivated in the Offinso Municipality of Ghana. Proximate and mineral compositions were analyzed, with significant differences found among vegetable types and irrigation water sources. Cabbage irrigated with tap water recorded the highest crude fibre, while amaranthus irrigated with rainwater recorded the highest carbohydrate and zinc contents. Wastewater irrigation significantly increased calcium content in amaranthus but corresponded to lower Vitamin C levels. Findings highlight the nutritional trade-offs associated with wastewater irrigation, underscoring the need to carefully consider water-source selection for vegetable farming. Further research should explore contamination risks and food safety implications. Int. J. Agril. Res. Innov. Tech. 15(2): 57-73, Dec 2025